209 A Review of Intravaginal Ejaculatory Dysfunction and Unconsummated Marriage Cases in the Outpatient Clinic for Male Infertility at the University of Tsukuba Hospital. (1st May 2022) - Kojo, K.; Oda, H.; Suetomi, T.; Negoro, H.; Nishiyama, H.
ABSTRACT: Introduction: Male infertility can be classified into three categories of causes: testicular factors, seminal tract obstruction, and sexual disorders. Sexual disorders, in particular, have been increasing in recent years, as people now marry later in life, and lifestyles have become more diverse. This study focused on erectile dysfunction (ED) and ejaculation dysfunction (EjD) because they are direct causes of sexual disorders and infertility. The most serious sexual disorders are intravaginal ejaculation dysfunction (IVEjD), which indicates a lack of ability to ejaculate during sexual intercourse, and unconsummated marriage (UM), which means no experience of sexual intercourse after marriage. In this study, we reviewed the actual statuses of IVEjD and UM in male infertility patients who were consulted at our clinic. Objective: To examine the characteristics of IVEjD and UM by comparing them with other male infertility patients. Methods: This study was approved by the relevant ethical review board. We obtained data on 83 male infertility patients diagnosed from 2018–2020 at our clinic. We extracted information on IVEjD and UM patients, which were defined as serious sexual disorders (SSD). We analyzed the factors of SSD cases related to infertility. Results: Of 83 male infertility cases, 26 cases had either ED or EjD. We found nine SSD cases; seven cases had IVEjD, and two cases had UM. The mean age was 38.8 years (IQR: 30–50), and the mean age of the wives was 33.6 years (IQR: 2–43). All SSD cases had never had ejaculatory intercourse with a woman including their wives. Seven cases possibly had ED or EjD, but all SSDs were able to ejaculate by masturbation. One case had premature ejaculation, and six cases had delayed ejaculation during masturbation. Three cases had poor semen findings (oligozoospermia or asthenozoospermia), one case had an organic abnormality (after phimosis surgery), and one case had active depression, but there were no abnormalities in the testicular volume or endocrine findings. The causes of SSDs were inappropriate methods of masturbation in three cases (push method in two cases, strong grip in one case), a lack of sexual experience in two cases, and sexual aversion in one case. In three cases, the wives were able to conceive, but all had undergone fertility treatments without sexual intercourse. Conclusion: In this study, 31.3% of male infertility patients had sexual disorders, which is higher than the figure in the national survey. In addition, 10.8% of men had never had sexual intercourse with ejaculation in their lives, and even if we consider the fact that these are patients who visit specialized outpatient clinics, it is clear that there are more patients suffering from SSD than expected. Although sexual disorders can be caused by physical abnormalities such as neurological disorders, vascular disorders, and endocrine disorders, all nine cases examined in this study were able to ejaculate by masturbation, suggesting that lifestyle and psychological problems are the major factors of infertility. Given the difficulty in providing medical interventions for these factors, only a small percentage of cases with severe sexual dysfunction resulted in pregnancy, suggesting the difficulty involved in treating sexual dysfunctions. Disclosure: Work supported by industry: no.